Gestión de ventas y su influencia en la rentabilidad financiera de la empresa APRONAM S.A. en el año 2022 de la ciudad de Chone - Álava Párraga, Bagner José (2025)
The present research is based on the study of sales management and its influence on financial profitability in the company APRONAM S.A., it was done through methodological development in compliance with three specific objectives. In the first phase of the research, a situational diagnosis was carried out, based on a bibliographic review that allowed the key indicators related to the general themes of the study to be identified. This input was essential to design the research instrument, in this case, an interview directed at the managers of APRONAM S.A. In addition, a SWOT analysis was prepared to evaluate the strengths, weaknesses, opportunities and threats of the company in its current context. In the second phase, interviews were applied, obtaining relevant information about sales management and the financial situation of the organization. Subsequently, the financial statements were analyzed, which facilitated the application of financial indicators to evaluate their performance. In the third phase, an action plan was designed using the 5W+1H matrix, detailing specific strategies and proposing a monitoring system to improve operations, optimize sales management and strengthen the financial profitability of APRONAM S.A.